Endothelin-1-induced PMN infiltration and mucosal dysfunction in the rat small intestine - (:unkn) unknown (AMER PHYSIOLOGICAL SOC, 2000)
The objectives of this study were to characterize the effects of endothelin (ET)-1 on intestinal mucosal parameters and to assess the contribution of polymorphonuclear leukocytes (PMNs), intercellular adhesion molecule-1 (ICAM-1), and a platelet-activating factor (PAF) to the mucosal dysfunction induced by ET-1. Different concentrations of ET-1 (100, 200, and 400 pmol/kg) were infused into the superior mesenteric artery for 10 min, and tissue samples were obtained 30 min after terminating the infusion. ET-1 administration significantly elevated tissue myeloperoxidase activity, plasma carbonyl content, and tissue chemiluminescence intensity, indicating that ET-1 produces PMN infiltration and oxidant stress. Blood-to-lumen clearance of Cr-51-EDTA significantly increased after ET-1 infusion (400 pmol/kg). Monoclonal antibodies against ICAM-1 (1A29, 2 mg/kg), antineutrophil serum, and PAF antagonist (WEB-2086, 10 mg/kg) attenuated the mucosal barrier dysfunction induced by ET-1. Overall, our data indicate that ET-1 causes PMN accumulation, oxidant stress, and mucosal dysfunction in the rat small intestine and that ET-1-induced mucosal dysfunction involves a mechanism that includes a role for PMNs, ICAM-1, and PAF.
Keywords: oxidant stress; mucosal permeability; intercellular adhesion molecule-1; platelet-activating factor; PLATELET-ACTIVATING-FACTOR; NITRIC-OXIDE; POLYMORPHONUCLEAR LEUKOCYTES; ENDOTHELIAL-CELLS; INJURY; PATHOGENESIS; INHIBITION; RELEASE